Explanation and argumentation strategies in the discourse of mathematics. Linguistic resources of orality and writing used for teaching and learning in the first years of engineering careers - Matiolli, Estela (Universidad Nacional del Litoral, 2021)
This article gives an account about a research which defines its object on the Universidad Nacional del Litoral, based on its relations with the local and socio-political sphere. This relationship expresses an instituting link in a double sense: society challenges university institution and it, in turn, contributes to the constitution of society of which it is a part. This perspective allows to identify and investigate the intersection areas between academic production and cultural and political intervention, considering as well the complex relationship between university and the changing political scenarios of the 20th century in Argentina. In order to develop the research, contributions from renewd political history, history of concepts, intelectual history and discourse analysis are recovered. This project will recover the results that the work team has achieved in previous research experiences, which have addressed characteristics of science discourse in different disciplines and the most productive ways of communicating it to university students for the purpose of collaborate in its interpretation and rewriting, promoting the construction of specific scientific-disciplinary knowledge. In this opportunity, the explanation and argumentation strategies in the discourse of mathematics will be analyzed, as well as the linguistic resources of orality and writing used for teaching and learning in the first years of engineering careers in the Facultad de Ingeniería y Ciencias Hídricas of Universidad Nacional del Litoral. This interdisciplinary work between Language and Mathematics teachers seeks to describe the ways used by experts and learners to explain and argue, identifying the aspects that present the greatest difficulty both in oral and written discourse, mediated or not by ICT, in order to later elaborate proposals for teaching that will be developed within each subject (Comunicación Oral y Escrita and the six Matemáticas) that promote student’s performance. The work will be framed in the perspective offered by Systemic Functional Linguistics, in addition to considering contributions of the specific didactics field and possibilities of using information and communication technologies (ICT).